Implementación de un Sistema de Gestión Académica bajo la Metodología Scrum en La Unidad Educativa a Distancia de Cotopaxi Monseñor Leónidas Proaño Extensión La Maná. - Lutuala Toaquiza, Juan Carlos (2019)
In the Distance Learning “Monseñor Leónidas Proaño” Educative Unit Extension La Maná Education, there are specific schedules where teachers provide tutoring to parents, and it is difficult for them to go to the institution in search of teachers to obtain knowledge about the academic activities carried out by their children. Therefore, the present project proposes to develop a mobile application that allows to monitor the academic activities of the students of the Unit by means of notifications in real time to the parents. The motivation of this proposal was to contribute to the process of communication of the teachers with the parents and thus to know the academic activities of the students in real time of the institution. The bibliographic information gathered in several sources such as scientific articles, theses, books and online sources is detailed in the theoretical basis. These bibliographic sources are listed in the respective section of this document. For the development of the application in a web environment the methodologies that have been used are directed to the systems area; it was taken as a guide for the Scrum development model for the Web. Within the research methodology has been used instruments such as: survey and interview the same that is addressed to teachers and parents of the institution. At the moment of the implementation and training of the users could be observed the acceptance before the web environment.